Cervicovaginal and gastrointestinal microbiomes in gynecological cancers and their roles in therapeutic intervention - Alhamlan, Fatimah S.; Albadawi, Ismail A.; Al-Qahtani, Ahmed A.; Awartani, Khalid A.; Obeid, Dalia A.; Tulbah, Asma M. (Frontiers in Microbiology, 2024)
Cancer remains a significant global health concern, and understanding factors that regulate cancer development is important. The microbiome, with its potential role in cancer development, progression, and treatment, has garnered increasing attention in recent years. The cervicovaginal and gastrointestinal microbiomes in females constitute complex biological ecosystems. Although the gut microbiome has been extensively studied, little is known about the cervicovaginal microbiome. The microbiome plays a crucial role in maintaining local microenvironments and tissue homeostasis, but dysbiosis can disrupt this fine balance and contribute to pathological ramifications leading to cancer. This review explores the current understanding of the microbiome’s correlation with gynecological cancers and highlights the potential of microbiome-based interventions to improve outcomes in these cancers. In addition, this review underscores the gaps and limitations in the literature, such as findings in specific ethnicities compared with understudied ethnicities. In addition, discrepancies in molecular techniques and terminology (microbiome vs. microbiota) used in the literature are addressed. Emerging evidence linking gynecological cancers and dysbiosis underscores microbiota as a potential target for cancer prevention and therapy. Manipulating the microbiome, such as through the use of probiotics, prebiotics, antibiotics, or vaginal and fecal transplantation, has demonstrated benefits in the treatment of chronic and inflammatory conditions. Further translational research in this field is needed to integrate the benefits of beneficial microorganisms in the fight against gynecological cancers.